On the diffusive Nicholson's blowflies equation with distributed delay. (December 2015) - Deng, Keng; Wu, Yixiang
Abstract: We study the global attractivity of the positive steady state of the diffusive Nicholson's equation with distributed delay. For such a problem, the monotone case has been solved while the non-monotone one remains open, which is the consideration of this paper.